Emotional innovation and its relationship to optimism and pessimism among students of the College of Basic Education (Journal of the College of Basic Education, 2022)
research targeted the following:Know Emotional Creativity when students Basic Education College.Know the differences in Emotional Creativity among students of the Faculty of Basic Education according to the type variable (male-female).Know optimism among students of Basic Education College.Know the differences in optimism among students of the Faculty of Basic Education according to the type variable (male-female).Know pessimism among students of Basic Education College.Know the differences in pessimism among students of the Faculty of Basic Education according to the type variable (male-female).Know the relationship between Emotional Creativity, optimism and pessimism among students of Basic Education College.After researchers completed the construction of Emotional Creativity scale and the scale of optimism and the measure of pessimism in its final form was applied to the sample applied the (320) students were selected stratified randomly, distributed according to specialization variables, the stage and sex, of the College of Basic Education departments search results emerged as Comes:-The students of the College of Basic Education have Emotional Creativity.There are significant differences in Emotional Creativity between males and females in favor of females.The students of College of Basic Education have optimism.There are significant differences in optimism among males and females in favor of females.The students of College of Basic Education of the innovators do not feel pessimistic.There is no significant difference in pessimism among males and females.There is a strong and positive correlation between Emotional Creativity and optimism, there are also negative and weak correlation between innovation and emotional pessimism and between optimism and pessimism.Through what has been reached from the results of researchers developed a set of recommendations and proposals.